Ultrasound of Thyroid Nodules - Bojunga, Jörg (Ultraschall in der Medizin - European Journal of Ultrasound, 2018)
Thyroid nodules are a common finding in the general population. Ultrasonography is the most sensitive imaging tool for diagnosing thyroid nodules. However, sonographic differentiation of hormonally active versus inactive nodules, and in particular benign versus malignant nodules, remains unreliable. In this context, thyroid scintigraphy has its clinical significance predominantly in diagnosing hormonal activity of thyroid nodules. However, most nodules are benign and a significant number of patients undergo surgery for diagnostic rather than for therapeutic reasons. Efforts of the past years aimed to improve sonographic risk stratification, to predict malignancy of thyroid nodules through standardized diagnostic assessment of validated risk factors, in order to select patients who require further diagnostic workup. In the last years, several imaging and reporting systems, giving standardized categories with rates of malignancy, were evaluated as a basis for further clinical management. Recent technological developments, such as elastography, also show promising data and might be implemented into clinical practice. Ultrasound-guided fine needle aspiration is the key element in the diagnosis of sonographically suspicious thyroid nodules and significantly contributes to the diagnosis of malignancy versus benignity.Schilddrüsenknoten sind ein häufiger Befund in der Allgemeinbevölkerung. Die Sonografie ist dabei das wichtigste und sensitivste bildgebende Instrument der Schilddrüsendiagnostik. Eine sichere Unterscheidung hormonaktiver und inaktiver Knoten sowie insbesondere benigner und maligner Knoten ist jedoch sonografisch bisher nicht ausreichend sicher möglich. Die klinische Bedeutung der Szintigrafie liegt daher in der Differenzialdiagnose der Hormonaktivität von Schilddrüsenknoten. Insgesamt ist das Risiko eines Schilddrüsenknotens in der Allgemeinbevölkerung, maligne zu sein, als sehr gering einzustufen. Zur Risiko-Stratifizierung des Malignitätsrisikos von Knoten wurde daher in den vergangenen Jahren versucht, durch standardisierte Befunderhebung evaluierter Risikofaktoren eine bessere Selektion von Patienten, die einer weiteren Diagnostik zugeführt werden sollen, zu erzielen. Neuere technische Verfahren wie die Elastografie zeigen ebenfalls vielversprechende Daten und könnten Eingang in den klinischen Alltag gewinnen. Die sonografisch gesteuerte Feinnadelpunktion ist aktuell jedoch weiterhin das zentrale Element in der Diagnostik sonografisch suspekter Schilddrüsenknoten und trägt wesentlich zur Sicherung der Diagnose Malignität vs. Benignität bei.